Generic characters of the Chrysomelidae - Failyer, Corinne (My University, 1903)
Introduction: TRIBE I. DONACIINI. The members of this tribe are graceful, active insects. The prominent head is narrowed behind the eyes. The eyes are entire. The antennae are close together and on the front before the eyes. The legs are long and frequently the hind thighs are toothed. Sometimes the front and hind tibiae are distinctly spurred. The tarsal claws are simple and the front coxal cavities are closed. The elytra are wider than the prothorax. Upon the elytra are ten rows of quadrate punctures. The epipleurae are narrow and indistinct. The genera Donacia and Haemonia are the only members of this tribe. The only ones in this tribe are separated by the characters of the feet. In the former the tarsi are dilated and spongy beneath, while the Haemonia the corresponding parts are narrow and glabrous. TRIBE II. SAGRINI. The genera of this tribe found in the tropics are large and splendidly colored. Those found here are small and dull of color. The back of the head is not narrowed. The eyes entire and the epistoma is large and distinct. The antennae are filiform and rather far apart on the front in advance of the eyes. The prothorax is no narrower than the head but the elytra are wider than the prothorax. The elytra are strongly punctured and are margined. The epipleurae are entire, narrow and distinct. The middle and hind coxae are but narrowly separated. The tibiae have no spurs and the tarsi are dilated. In this tribe are the genera, Orsodaena, Zengophone, Syneta and Thricolema. In the Sagrini the generic distinctions are based on the separation of the coxae, the form of their cavities, the shape and sculpture of the prothorax, the form of the eye and the character of the claws.
Citation: Failyer, Corinne. Generic characters of the Chrysomelidae. Senior thesis, Kansas State Agricultural College, 1903.
Morse Department of Special Collections
Keywords: Donaciini; Sagrini; Criccerini; Theses; Manuscripts (documents)